A geografia nas séries iniciais do ensino fundamental: desafios da e para a formação docente - Novaes, Ínia Franco de (2006)
The presence and the peculiar characteristics of the geographical science in the educat ional context have always made me to quest ion some procedures, because they are int roduced to the students in an isolated and artif icial way thus hinder ing learning. We aim at knowing Geography in the school daily life of six teachers in the init ial series of the elementary school, which were in the beginning of their studies. The methodology that was chosen for the accomplishment of the research was the Thematic Oral History that allows the researcher to know the recent past of their subjects, studying their speeches to have information with dif ferentiated points of view that, on their turn, are related to a specif ic theme school Geography. The work begins with a map of the scientif ic researches produced in Brazil which are related to the teaching of Geography in the initial series of the elementary school, trying to analyze and discuss the theoretical conceptions that permeated the researches. We, then, made a ref lection on the new research perspectives in the educational cont inuing studies, History of Life, and the collaborat ion of the methodology of the Thematic Oral History for the understanding of the teachers' geographical trajectory. We studied the History of Education in Brazil delineat ing ref lections of theoretical order, with a synthesis of the development of the educat ion in the init ial series of the elementary school, analyzing the inf luence of laws and ordinances in that teaching level and, consequently, in school Geography. Finally, we characterized the inst itutionalizat ion of the course of Pedagogy in Brazil and in the Universidade Federal de Uberlândia, as well as the trajectory of the discipline that discusses Geography in the referred course, accomplishing a reading of the environment of the initial studies in order to know the context and perspectives which are related to Geography in the educat ional continuing studies. The work was delineated by the geographical school life of the six teachers who were selected by the questionnaire that was applied to the students of the discipline Didática e Metodologia de Geografia e História in the last year of kindergarten and f irst four years of the elementary level, in 2004. We concluded that there are several factors that direct ly interfere in the depreciation of Geography on the school environment and on the teachers' practices that act in the initial ser ies of the elementary level. Those factors are related to the contact that those professionals had with geographical knowledge dur ing their schooling process and initial studies. We understand that Geography should be taught since the Init ial Grades, because that school discipline allows us to understand the dynamics of contemporary social space, despite the analysis scale. Geography in the Initial Ser ies has a contribution to offer: the one of geographically alphabetizing the students, making them do develop the capacity to observe, read, and understand the environment, once the student should act as a citizen in society.